a) + ( + 9 ) – ( + 6 ) =
b) – ( + 7 ) + ( - 3 ) =
c) + ( - 5) – ( - 5 ) =
d) – ( - 2 ) – ( - 8 ) =
e) + ( - 4 + 9 ) – ( + 6 ) =
f) – ( - 10 ) + ( + 3 – 15 ) =
g) – ( - 3 + 11 – 8 + 6 ) =
h) + ( - 1 + 4 ) – ( + 17 – 6 ) =
g) – ( - 8 + 3 ) + ( - 5 – 19 ) =
Respuestas a la pregunta
Contestado por
1
Respuesta:
15 10 0 0 4 5 6 12 9
Explicación paso a paso:
Otras preguntas
Ciencias Sociales,
hace 3 meses
Química,
hace 3 meses
Matemáticas,
hace 3 meses
Física,
hace 5 meses
Biología,
hace 11 meses
Matemáticas,
hace 11 meses